The Birth of Sociology from the Spirit of (Critique of Bourgeois) Philosophy? The Belarusian Case in the 1960s through 1980s - Dudchik, Andrei (Stan Rzeczy, 2017)
This article covers the development of sociology as a scientific discipline in Belarus in the period of the 1960s through 1980s. It analyses the close interrelation between sociological and philosophical knowledge. It also looks at the phenomenon of the double identity of the sociologist and the philosopher, leading to their reciprocal influence. The indirect influences of Western sociological and philosophical conceptions are explained as an important source of sociology’s development. Analysis shows that some Western ideas were known rather well and were presented in academic publications and textbooks in the form of “criticism of bourgeois science,” which, despite its critical form, could often provide real information. Analysis of the main texts (monographs, textbooks, and dictionaries, as well as memoirs) helps to cover the main problems, approaches, works, and concepts that were transferred to, and referred to, in Belarusian sociology in the period of the 1960s through 1980s. The process of transfer had a slow but permanent and constant character and the usage of Western conceptions became ever more normal and legitimated. The findings reveal the real importance of “Western” knowledge as a “shadow” factor in the development of sociology (often in close connection with philosophy) in Soviet Belarus in the 1960s through 1980s.